A Phenyl‐Ethynyl‐Macrocycle: A Model Compound for "Geländer" Oligomers Comprising Reactive Conjugated Banisters. Issue 26 (21st June 2018) - Bannwart, Linda Maria; Jundt, Lukas; Müntener, Thomas; Neuburger, Markus; Häussinger, Daniel; Mayor, Marcel
Abstract : Macrocycle1 is assembled as smallest member of a series of "Geländer" oligomers with a conjugated banister comprising exclusively sp 2 ‐ and sp‐hybridized carbon atoms. The synthesis of1 is based on an acetylene scaffolding approach, comprising Sonogashira cross‐coupling reactions in combination with protection group strategies and a final cyclization based on an oxidative acetylene coupling using Eglinton‐Breslow reaction conditions. Macrocycle1 serves as model compound for the investigation of the structural integrity of the strained 1, 3‐diyne subunit. An enhanced reactivity of the strained 1, 3‐diyne subunit is documented by its engagement in Huisgen's (2+3) cycloaddition when exposed to an azide at elevated temperature. Both structures, macrocycle1 and cycloaddition‐product2, are fully characterized including their solid‐state structure obtained by X‐ray diffraction analysis. Abstract : The conjugation in the helical banister of "Geländer" oligomers is reflected in the compounds electronic and optical properties. The synthesized diyne macrocycle1 serves as model compound for the development of the chemistry, and to investigate the reactivity of the strained dialkyne subunit, enabling e.g. its engagement in [2+3] cycloadditions.